Use of Methods Everyone Is A Teacher Here To Improve Geography Learning Outcomes - Miftahul Jannah (Syntax Corporation Indonesia, 2021)
Education plays an important role to realize the government's efforts in educating the nation's life and ensuring the survival of the nation and the State. Education is also a long-term investment for the government and a vehicle to improve and develop the quality of human resources. The purpose of Geography education in schools in general is that students are expected to be able to understand concepts about the symptoms of nature and life on earth as well as interactions between humans and their environment that are closely related to the aspects of space and time. The research on the application of Everyone Is A Teacher Here Method in Geography learning in class XI IPS 1 SMAN 1 Rengat Barat is classroom action research, which is a study conducted by the teacher himself to improve the learning process that is his responsibility. The use of everyone is a Teacher Here method learning can improve students' learning outcomes in Geography learning in Grade XI IPS 1 SMAN 1 Rengat Barat, also make the teacher's activity in delivering student center-oriented materials significantly improved.